Stable accumulation of a rat truncated repeat transcript in Xenopus oocytes. - Gutierrez-Hartmann, A (1986)
To define potential mechanisms of expression of middle-repetitive DNA, Xenopus oocytes were employed to examine the rat type 2 and truncated repeat (TR) elements contained in an intron and in the 3'-flanking region of the rat growth hormone gene. These repeats contain significant sequence and structural homology to tRNA genes and, thus, may represent tRNA pseudogenes. Transcripts from the type 2 elements do not accumulate in the cytosol and are found predominantly in the nucleus, whereas those from TR DNA are expressed in the cytosol of neural and pituitary tissues. In HeLa cell extracts, the rat growth hormone type 2 sequences initiate RNA polymerase III transcription resulting in multiple transcripts of 175-970 nucleotides; some of these also contain TR sequences that are present only as downstream structures since the rat growth hormone-TR DNA lacks promoter activity. In Xenopus oocytes the same template also results in multiple transcripts, but with time a single, homogeneous 73-base RNA preferentially accumulates. This RNA probably arises from larger repetitive DNA transcripts as assessed by the kinetics of its formation, its 5' terminus, and the injection of transcripts generated in HeLa cell-free extracts into the oocytes. Sequence analysis of the 73-base RNA suggests that it is a TR transcripts derived from the TR region with tRNA homology. Stable type 2 transcripts were not detected. Thus, type 2 elements are transcribed in the oocytes, but RNAs from them are degraded whereas discrete TR DNA transcripts can be derived from larger RNA molecules and can accumulate in the cytosol due to their preferential stability. These findings indicate that posttranscriptional control mechanisms can operate to direct differential expression of closely related repetitive DNAs and suggest that structures similar to tRNA contained within the TR sequences may allow them to accumulate preferentially in the cytoplasm.